Atividade de óleo essencial de Lippia gracilis e seus monoterpenos majoritários associados à carrapaticidas sintéticos em Rhipicephalus microplus (Acari: Ixodidae) - MILHOMEM, Marlise Neves Milhomem (2017)
The Rhipicephalus microplus tick is considered one of the biggest problems for cattle breeding in Brazil. The continuous use of synthetic acaricides to control this tick has increased the frequency of resistance. Work using extracts and plant oils, are shown to be promising in the control of R. microplus. Lippia gracilis is a plant rich in essential oil, presenting major compounds which have a proven carrapaticide effect. The objective of this work was to evaluate the effect of the association between synthetic carrapaticides and natural compounds on resistant and susceptible synthetic Rhipicephalus microplus larvae. Immersion tests of R. microplus larvae were carried out using synthetic carrapaticides and essential oils (OE) of L. gracilis and their major compounds. First the lethal concentration to 50% (LC50) of the larvae was found for each of the isolated compounds. Associations of each of the natural compounds associated with a synthetic carrapaticides. In the obtained results it is observed that there was an antagonistic effect in the associations with one of the synthetic carrapaticides used, however in the associations with the other carrapaticide a strong synergic effect is observed, the same occurred for the two strains. We have shown that associations of natural compounds with synthetic carrapaticides may be a promising alternative in the control of R. microplus